Who is the buddha? - Sangharakshita (Birmingham : Windhorse Publications, 1995)
The image of Buddha, cross-legged and meditating, is a familiar one in the West. But who was the Buddha? In this book, Buddha is presented as a historical figures and as an archetype. The author places him in the context of time and eternity.
includes notes, references and index.
Keywords: Buddha and Buddhism; Buddhism -- Deities